Reproductive biology of Black-necked Swans Cygnus melancoryphus at three Chilean wetland areas and feeding ecology at Rio Cruces - Schlatter, Roberto P; Salazar, Juan; Villa, Alex; Meza, Javiera (Wildfowl, 2013)
Reproductive biology o f Black-necked Swans has been monitored at three sites in Chile, Laguna El Peral, Laguna Torca and Rio Cruces. The eight pairs at El Peral have produced 4.2 cygnets/pair in three seasons, but chick mortality has been 83 % due to territoriality and aggressive interactions. At Torca on average 15 pairs have produced 3.4 cygnets/pair with mortality of 12% for only one surveyed season. At Rio Cruces nests have more than doubled each season increasing from 55 (1986-87 season), 120 (1987-88) to 243 (1988-89). Pairs have also increased: 118 (1985-86), 90 (1986-87), 167 (1987-88) up to 250 (1988-89 season) with different degree of reoccupation for nests. Average number of eggs/pair was 5.4 eggs (1986-87), 2.9 (1987-88 season) and 2.4 for the 1988-89 season. Average cygnet mortality has been low, about 8% (1986-87) and5% (1987-88) for a strongly increasing population. Predation of eggs by Polyborus plancus is considered important. The Rio Cruces Black-necked Swan population feeds mainly on introduced Egeria densa weed (99% of faecal samples). Food is abundant and does not seem to be important in regulating stable breeding populations. Adult aggression towards cygnets and juveniles is an important mortality factor in small areas. Some of the cygnets found dead showed skeletal deformation perhaps due to malnutrition.